Epidemiologic, Diagnostic and Therapeutic Aspects of Paediatric Femoral Shaft Fractures at The Yaounde Gynaeco-Obstetric and Paediatric Hospital - Dongmo, Gael; Mouafo Tambo, Faustin Félicien; Ngowe Ngowe, Marcelin; Nkemtedong Tolefac, Paul; Ngo Nonga, Bernadette; Ze Minkande, Jacqueline (HEALTH SCIENCES AND DISEASE, 2018)
RÉSUMÉ Introduction. Femoral shaft fractures (FSF) are common in the paediatric age group. They represent 1.4 to 1.7% of fractures in children and 20% of children hospitalize for fractures. It is a traumatologic emergency, whose diagnosis is clinical and the prognosis is generally good. The aim of the study was to describe the epidemiologic, diagnostic and therapeutic aspects of FSF in children at the Yaounde Gynaeco–Obstetric and Paediatric Hospital (YGOPH). Methods. This was a retrospective descriptive study from 2004 to 2016 and prospective study from November 2016 to February 2017. It was conducted at the paediatric surgical service of the YGOPH. We included patients aged 0 to 15 years of age who were treated in the service, excluding those who were discharged against medical advice. Results. FSF represented 67 (91.8%) of femoral fractures. The mean age was 4.7±4.3 years among which 46 (68.7%) were males. 41 (61.2%) were schooling. The main circumstance of occurrence was road traffic accident 32(47.8%). Clinically, deformity (94%) predominated. (65%) of fractures affected the right limb. The most common radiological sign was: the visibility of the transverse line of fracture (70.1%). Displacement was overlap in 31.3% of cases. The treatment was always orthopaedic (100%). The morbidity was mainly valgus angulation (16.5%). Conclusion. FSF occur mostly in male children of 4.7 years as a result of road traffic accidents. The diagnosis is clinical and the role of plain radiography is to assess fracture line and displacement. The treatment is usually orthopaedic. ABSTRACT Introduction. Les fractures de la diaphyse fémorale (FDF) sont fréquentes chez l’enfant. Elles représentent 1.4 à 1.7% des fractures chez l’enfant et 20% des patients hospitalisés. C’est une urgence traumatologique. Le diagnostic est clinique et le pronostic est bon. Le but de l’étude était de décrire les aspects épidémiologiques, diagnostiques et thérapeutiques des fractures de la diaphyse fémorale chez l’enfant à l’Hôpital Gynéco-Obstétrique et Pédiatrique de Yaoundé (HGOPY). Méthodologie. Il s’agit d’une étude transversale rétrospective descriptive de 2004 à 2016 et prospective de Novembre 2016 à Févier 2017. Elle a été menée dans le service de chirurgie pédiatrique de l’HGOPY chez les enfants âgés de 15 ans ou moins. Les variables d’intérêt étaient les aspects sociodémographiques, diagnostiques et thérapeutiques des enfants souffrant de fractures de la diaphyse. Résultats. Les FDFs représentaient 67 (91.8%) des fractures fémorales. L’âge moyen était 4.7±4.3 ans parmi lesquels 46 (68.7%) étaient de sexe masculin. 41 (61.2%) étaient scolarisés. La circonstance de survenue la plus fréquente était les accidents de la voie publique 32(47.8%). Cliniquement, la déformation (94%) prédominait. (65%) des fractures étaient à droite. Le trait: (70.1%) transverse prédominait. Le chevauchement (31.3%) était le déplacement le plus fréquent. Le traitement était orthopédique (100%). L’angulation valgus était la morbidité la plus fréquente (16.5%). Conclusion. Les FDFs sont fréquentes chez le garçon de 4.7 ans survenu à la cour d’un accident de la circulation. Le diagnostic est clinique et fait appel à la radiographie standard pour préciser le trait et le déplacement. Le traitement est essentiellement orthopédique.